Organic reactions (John Wiley & Sons, Inc, 2002)
Organic Reactions is a comprehensive series devoted to important synthetic reactions, each volume having wide applicability. Each chapter focuses on a single reaction or a definitive phase of a reaction, and each is written by world-renowned chemists with extensive hands-on experience in their specialties. The material is presented from a preparative point of view, and particular attention is given to reaction limitations, interfering influences, effects of chemical structure, and the selection of experimental conditions. Each reaction includes information about its conditions, products, and yields, where available, and is fully referenced to the primary literature. The authors also include detailed procedures illustrating the significant modifications of the chemical reaction, as well as tables featuring all pertinent data about the reaction.